Psychosocial impact of cicatricial alopecias - Pratibha Pradhan; Mariette D'Souza; Bhawana Ashok Bade; Devinder Mohan Thappa; Laxmisha Chandrashekar (Wolters Kluwer Medknow Publications, 2011)
Background: Cicatricial alopecias have a significant impact on the psychological status, quality of life, and social interaction of those suffering from it. Till date, limited or no data have been available regarding the psychosocial and quality of life aspects of cicatricial alopecias. Aims: To assess the psychosocial impact of cicatricial alopecias. Materials and Methods: Thirty patients fulfilling the criteria for cicatricial alopecia irrespective of their age and sex were included in the study. Psychosocial assessment was carried out in 23 patients who were capable of responding to the questionnaire, using an adopted and suitably modified version of Women's Androgenetic Alopecia Quality of Life Questionnaire. Results : We observed that 73.9% of our patients with cicatricial alopecias had moderate to severe psychosocial impact due to their hair loss. Patients of younger age group and with inactive disease, suffered from greater psychosocial impact of the disease. Patients with slight hair loss also had considerable psychological distress. The chronicity of disease duration did not seem to reduce the psychosocial impact of the disease. Both married and unmarried patients suffered equally from the psychosocial impact of the disease. Conclusion: The management of cicatricial alopecias needs a holistic approach. In addition to laying an emphasis on early diagnosis aided by clinco-pathological correlation, to prevent irreversible hair loss, the psychosocial impact of the disease should also be taken into consideration and addressed by the treating dermatologist.